Electrochemically modified Corey–Fuchs reaction for the synthesis of arylalkynes. The case of 2-(2,2-dibromovinyl)naphthalene - Pandolfi, Fabiana; Chiarotto, Isabella; Feroci, Marta (Beilstein Journal of Organic Chemistry, 2018)
The electrochemical reduction of 2-(2,2-dibromovinyl)naphthalene in a DMF solution (Pt cathode) yields selectively 2-ethynylnaphthalene or 2-(bromoethynyl)naphthalene in high yields, depending on the electrolysis conditions. In particular, by simply changing the working potential and the supporting electrolyte, the reaction can be directed towards the synthesis of the terminal alkyne (Et4NBF4) or the bromoalkyne (NaClO4). This study allowed to establish that 2-(bromoethynyl)naphthalene can be converted into 2-ethynylnaphthalene by cathodic reduction.
Keywords: arylalkyne; carbon–bromine bond cleavage; cathodic reduction; Corey–Fuchs reaction; 2-(2,2-dibromovinyl)naphthalene

(untitled) - Lei, J.; Su, L.; Zeng, K.; Chen, T.; Qiu, R.; Zhou, Y.; Au, C.-T.; Yin, S.-F. (Chem. Eng. Sci., 2017)

(untitled) - Chinchilla, R.; Nájera, C. (Chem. Rev., 2014)

(untitled) - Ackermann, L. (Acc. Chem. Res., 2014)

(untitled) - Rodríguez, M. R.; Beltrán, Á.; Mudarra, Á. L.; Álvarez, E.; Maseras, F.; Díaz-Requejo, M. M.; Pérez, P. J. (Angew. Chem., Int. Ed., 2017)

(untitled) - Islas, R. E.; Cárdenas, J.; Gaviño, R.; García-Ríos, E.; Lomas-Romero, L.; Morales-Serna, J. A. (RSC Adv., 2017)

(untitled) - Takano, S.; Kochi, T.; Kakiuchi, F. (Chem. Lett., 2017)

(untitled) - Liu, H.; Lu, L.; Hua, R. (Tetrahedron, 2017)

Org. Synth. - Campbell, K. N.; Campbell, B. K. (1963)

(untitled) - Müller, S. G.; Liepold, B.; Roth, G. J.; Bestmann, H. J. (Synlett, 1996)

(untitled) - Roth, G. J.; Liepold, B.; Müller, S. G.; Bestmann, H. J. (Synthesis, 2004)

(untitled) - Corey, E. J.; Fuchs, P. L. (Tetrahedron Lett., 1972)

(untitled) - Sahu, B.; Muruganantham, R.; Namboothiri, I. N. N. (Eur. J. Org. Chem., 2007)

(untitled) - Zhao, M.; Kuang, C.; Yang, Q.; Cheng, X. (Tetrahedron Lett., 2011)

(untitled) - Morri, A. K.; Thummala, Y.; Doddi, V. R. (Org. Lett., 2015)

(untitled) - Heravi, M. M.; Asadi, S.; Nazari, N.; Lashkariani, M. B. (Curr. Org. Chem., 2015)

(untitled) - Steckhan, E.; Arns, T.; Heineman, W. R.; Hilt, G.; Hoormann, D.; Jörissen, J.; Kröner, L.; Lewall, B.; Pütter, H. (Chemosphere, 2001)

(untitled) - Frontana-Uribe, B. A.; Little, R. D.; Ibanez, J. G.; Palma, A.; Vasquez-Medrano, R. (Green Chem., 2010)

(untitled) - Schäfer, H. J. (C. R. Chim., 2011)

(untitled) - Horn, E. J.; Rosen, B. R.; Baran, P. S. (ACS Cent. Sci., 2016)

The Chemistry of Functional Groups, Supplement D2 - Casanova, J.; Reddy, V. P. (Electrochemistry of the carbon−halogen bond, 1995)

Encyclopedia of Electrochemistry - Peters, D. G. (Oxidation and reduction of halogen-containing compounds, 2004)

Electroorganic Reduction Synthesis - Torii, S. (Electroreduction of Halogenated Compounds, 2006)

Organic Electrochemistry - Peters, D. G. (Taylor & Francis, LLC, 2016)

(untitled) - Martin, E. T.; McGuire, C. M.; Mubarak, M. S.; Peters, D. G. (Chem. Rev., 2016)

(untitled) - Feroci, M.; Orsini, M.; Palombi, L.; Sotgiu, G.; Inesi, A. (Electrochim. Acta, 2004)

(untitled) - Strobel, S. M.; Szklark, G. D.; He, Y. Q.; Foroozesh, M.; Alworth, W. L.; Roberts, E. S.; Hollenberg, P. F.; Halpert, J. R. (J. Pharmacol. Exp. Ther., 1999)

(untitled) - Beebe, L. E.; Roberts, E. S.; Fornwald, L. W.; Hollenberg, P. F.; Alworth, W. L. (Biochem. Pharmacol., 1996)

(untitled) - Mubarak, M. S.; Peters, D. G. (Curr. Opin. Electrochem., 2017)

Organic Electrochemistry - Gennaro, A.; Isse, A. A.; Mussini, P. R. (Taylor & Francis, LLC, 2016)

(untitled) - Abbas, S.; Hayes, C. J.; Worden, S. (Tetrahedron Lett., 2000)

(untitled) - Li, Y.-P.; Fan, X.-X.; Wu, Y.; Zeng, X.-C.; Wang, J.-Y.; Wei, Q.-H.; Chen, Z.-N. (J. Mater. Chem. C, 2017)

(untitled) - Kato, S.-i.; Noguchi, H.; Kobayashi, A.; Yoshihara, T.; Tobita, S.; Nakamura, Y. (J. Org. Chem., 2012)